Umbrella Monopole Antenna for 5G Applications - Paulen Aulia Lutfia; Nurhayati Nurhayati; Samuel Prasad Jones Christydass (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2021)
Umbrella Monopole Antenna (UMA) proposed in this paper for 5G application. We designed four models of UMA, i.e: UMA-A, UMA-B, UMA-C, and UMA-D. The antenna has a curvature in the patch as an umbrella shape with a feeding shape a microstrip feed line. Four variations of the patch antenna have been designed and get different performance in VSWR, surface current, and directivity. The proposed antenna has a wide bandwidth that operates 8 GHz 30 GHz with VSWR <2 dB. The Increasing of directivity is reached for UMA-A, UMA-C, UMA-D, and UMA-B, i.e: 6.38 dBi, 7.97 dBi, 8,84dBi, and 9,15 dBi respectively at 24 GHz.  The maximum gain has been reached for UMA-B of 9.15. The lowest frequency that has a return loss of 10 dB has resulted for UMA-D in the frequency around 5 GHz. All of the UMA antennas can be applied for 5G mmwave applications at 24 GHz and 28 GHz.